Single‐Crystalline Colloidal Quasi‐2D Tin Telluride. Issue 12 (17th May 2020) - Li, Fu; Fu, Jiecai; Torche, Abderrezak; Kull, Sascha; Kornowski, Andreas; Lesyuk, Rostyslav; Bester, Gabriel; Klinke, Christian
Abstract: Tin telluride is a narrow‐gap semiconductor with promising properties for infrared (IR) optical applications and topological insulators. A convenient colloidal synthesis of quasi‐2D SnTe nanocrystals through the hot‐injection method in a nonpolar solvent is reported. By introducing the halide alkane 1‐bromotetradecane as well as oleic acid and trioctylphosphine, the thickness of 2D SnTe nanostripes can be tuned down to 30 nm, while the lateral dimensional can reach 6 µm. The obtained SnTe nanostripes are single crystalline with a rock‐salt crystal structure. The absorption spectra demonstrate pronounced absorption features in the IR range revealing the effect of quantum confinement in such structures. Abstract : A convenient colloidal synthesis of quasi‐2D SnTe nanocrystals is reported. By introducing the halide alkane 1‐bromotetradecane as well as oleic acid and trioctylphosphine, the thickness of SnTe nanostripes can be tuned down to 30 nm, while lateral dimension can reach 6 µm. The absorption spectra demonstrate pronounced absorption features in the infrared range revealing the effect of quantum confinement.